Dr. Atkins' New Diet Revolution - Atkins, Robert C. M.D. (New York Avon Books, 1992)
A revolutionary formula for changing metabolism offers weight loss without counting calories or feeling hungry as the body automatically adjusts to a new way of burning fat, as well as a maintenance diet that ensures slimness for life.
Include Index and References.
Keywords: Reducing Diets -- Insulin Resistance